Rv1075c of Mycobacterium tuberculosis is a GDSL-Like Esterase and Is Important for Intracellular Survival. (18th April 2019) - Yang, Dong; He, Xiaoping; Li, Shaoji; Liu, Jiawang; Stabenow, Jennifer; Zalduondo, Lillian; White, Stephen; Kong, Ying
Abstract: Mycobacterium tuberculosis lipid metabolism pathways facilitate access to carbon and energy sources during infection. M. tuberculosis gene Rv1075c was annotated as a conserved hypothetical protein. We identified that Rv1075c amino acid sequence shares similarities with other bacterial lipase/esterases and we demonstrated that it has esterase activity, with preference for short-chain fatty acids, particularly acetate, with highest activity at 45°C, pH 9. Site-direct mutagenesis revealed its activity triad as Ser 80, Asp 244, and His 247 . We further determined that rRv1075c hydrolyzed triacetin and tributyrin, and it was mainly distributed in cell wall and membrane. Its expression was induced at pH 4.5, mimicking the acidic phagosome of macrophages. Mutation of Rv1075c led to reduced bacterial growth in THP-1 cells and human peripheral blood mononuclear cell-derived macrophages, and attenuated M. tuberculosis infection in mice. Our data suggest that Rv1075c is involved in ester and fatty acid metabolism inside host cells. Abstract : We have identified that a M. tuberculosis hypothetical protein Rv1075c acts as an esterase in lipid metabolism of M. tuberculosis, and is important for M. tuberculosis survival in the acidic niche in the phagosome.